USAHA PENGELOLAAN MAKANAN UNTUK MENINGKATKAN KUALITAS MAKANAN DI WARUNG MAKAN ULEGFOOD BANTUL - Shyuhri Syahrizal; Emmita Devi Hari Putri (Universitas Bina Sarana Informatika, 2014)
The quality of foodis strongly influencedbythe process offoodmanagement. The processof foodstorageplays an important rolein improvingthe qualityof food. Especiallyin theprocess of preparingthe rawmaterialbefore itis cookedinto afast foodmakesadecisiveearlystepin thetimeliness offoodpresentation. Food processingiscarried out correctlywillresult infoodthat suits your needs. In addition tothefoodprocessingalsotakesa goodselectionof rawmaterialsin order togeta good mealacylanyway. Presentation ofprepared foodsthatwilladd value tothe rightofthe food itself, so itcan attractcustomers.Therefore,thecomparisonswithother productswillwe knowthe extent of theeffortin managingfood.